MEMAKNAI KASIH ALLAH DI TENGAH PENGALAMAN BENCANA DALAM TERANG HOSEA 1:6-7 - Patrisius Epin Du (Aggiornamento, 2021)
The focus of this paper is to explore the experience of God's mercy in the midst of disaster. Disasters often make people suffer. This experience of suffering raises a question about God's mercy. Where is God in human suffering? In that situation, human beings try to maintain their faith or turn away from it and do not believe in God's love. Hosea 1: 6-7 provides an interesting reflection on the Israelites' experiences of suffering. The main objective of this research is to see God's act of mercy in the text of Hosea 1: 6-7 and its meaning for people who are in disaster situations. The experience of the Israelites become an image for everyone of how to deal with difficult events in life. The method used is descriptive qualitative with a semantic analysis approach and literature study. This study found several points in interpreting God's love in the midst of a disaster experience, namely: a) God is faithful in accompaning His people, b) God's love continues in human life. God's loyalty and love have made people steadfast in their faith even in facing of catastrophic events.